来华留学生学习成语分析 - Ade Prima Mardiana (Universitas Negeri Malang, 2022)
Abstract: Idioms are an important part of Chinese culture. Basic understanding of Chinese idioms, explaining that Chinese idioms have gradually grown with the development of Chinese traditional culture. This paper used method an questionnaire to collect data. The finding and discussion analysis of survey results is about examines the learning and use of idioms, and then proposes specific solutions through problems. And the conclusion is the cultivation of students' learning methods in the teaching of Chinese idioms. 摘要: 成语是汉语文化的重要组成部分。本文一共四个部分，第一部分：汉语成语的基本认识，该部分说明了汉语成语是随着汉语传统文化发展逐渐丰富起来的；第二部分：调查的基本情况，外国人和中国人交流之所以会出现误解，造成误解的原因主要是不了解成语的深刻含义；第三部分：调查结果分析，本论文只是对汉语成语学习和使用情况进行调查，然后通过问题提出具体的解决办法。第四部分：教学策略，即在教学汉语成语过程中对学生学习方法的培养。